Peran Musyrif dalam Membangun Lingkungan Berbahasa di Pondok Pesantren Riyadhussholihiin Kabupaten Pandeglang - Humaedi, Humaedi; Uyuni, Yuyun Rohmatul (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Islamic boarding schools (Pondok Pesantren) play a central role in creating a language-rich environment that supports language acquisition, particularly Arabic as the primary language of instruction in religious studies. This study aims to explore in depth the role of musyrif (student mentors) in developing a language environment within the pesantren and its impact on the students’ language skills. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation. The findings indicate that musyrif serve as role models in language use, introduce proper language practices, and supervise daily language interactions. The language environment created by the musyrif has been shown to significantly improve students’ language proficiency in both Arabic and Indonesian. Despite challenges such as varying student backgrounds and maintaining consistency in language policy, this study recommends enhancing musyrif training, introducing more flexible language learning approaches, and utilizing technology to support the language acquisition process in Islamic boarding schools.